Diffractometer for element-specific analysis on local structures using a combination of X-ray fluorescence holography and anomalous X-ray scattering - Hiroo Tajiri; Shinji Kohara; Koji Kimura; Sekhar Halubai; Haruto Morimoto; Naohisa Happo; Jens R. Stellhorn; Yohei Onodera; Xvsheng Qiao; Daisuke Urushihara; Peidong Hu; Toru Wakihara; et al. (Journal of Synchrotron Radiation)
To tackle disorder in crystals and short- and intermediate-range order in amorphous materials, such as glass, we developed a carry-in diffractometer to utilise X-ray fluorescence holography (XFH) and anomalous X-ray scattering (AXS), facilitating element-specific analyses with atomic resolution using the wavelength tunability of a synchrotron X-ray source. Our diffractometer unifies XFH and AXS configurations to determine the crystal orientation via diffractometry. In particular, XFH was realised even for a crystal with blurred emission lines by a standing wave in a hologram, and high-throughput AXS with sufficient count statistics and energy resolution was achieved using three multi-array detectors with crystal analysers. These features increase tractable targets by XFH and AXS, which have novel functionalities.